Analisis Kualitas Layanan Pengguna Website STAI Ma'arif Jambi Menggunakan Metode Webqual 4.0 dan IPA - Saloma; Kurniabudi; Sharipuddin (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2024)
The STAI Ma'arif Jambi website is one of the media that can be accessed using the internet. The website presents information in the form of text, images, audio, using the HTTP protocol. Therefore, the quality of the services provided must be of high quality so that website users feel satisfied with the services provided. The method used is the webqual 4.0 method and importance performance analysis (IPA). Based on data from calculations using the Slovin formula, the number of respondents required was 156 people, therefore questionnaires were distributed for more than one month to students and the general public. Where the distribution of the questionnaire was carried out at STAI Ma'arif Jambi and in the surrounding environment of Jambi. Data collection in this research was taken from the results of an online questionnaire using Google Form. As a result of distributing the questionnaire, 156 respondents were obtained, where the respondents were divided into two categories, namely men and women. The data was processed using IBM SPSS Statistics 23 software. The results of this research show that the variable that has the most influence on user satisfaction on the STAI Ma'arif Jambi website is the quality of interaction, with a calculated t value of 3.846%. This variable is more significant than usefulness at 2,799% and information quality at 3,070%. The analysis results also show that the highest ranking is in the quality of service interactions (X3) with a value of 1.08%, while the lowest ranking is in the quality of information (X2) with a value of 0.93%. The average gap value (GAP) of -0.39 indicates that the quality of website performance has not met user expectations. In addition, the IPA quadrant analysis emphasizes the need for improvements to indicators in the third quadrant, because low levels of performance can influence users' interest in relying on these indicators.